Characterization of Plebeiobacterium marinum gen. nov., sp. nov. and Plebeiobacterium sediminum sp. nov., revealing the potential nitrogen fixation capacity of the order Marinilabiliales - Yu, Wen-Xing; Liang, Qi-Yun; Du, Zong-Jun; Mu, Da-Shuai (Frontiers in Marine Science, 2023)
Biological nitrogen fixation plays a crucial role in the marine nitrogen cycle, impacting global marine productivity and related carbon fluxes. The strains were analyzed by gene annotation, growth conditions and phylogenetic analysis of 16S rRNA gene sequences.These two strains were isolated from the coastal sediment at Xiaoshi Island in Weihai, China. The strains were analyzed by gene annotation, growth conditions and phylogenetic analysis of 16S rRNA gene sequences. It was revealed that strains D04T and AATT contain a set of nif gene clusters responsible for nitrogen fixation. Cell are yellow-colored, Gram-stain-negative, facultatively anaerobic, and rod-shaped bacteria. The optimal growth conditions for strain D04T were found to be at 33 °C, pH 7.0, and in 2% (w/v) NaCl, while strain AATT prefers growth conditions at 33 °C, pH 6.5, and in 3% (w/v) NaCl. The highest similarity of strains D04T and AATT was to Saccharicrinis fermentans NBRC 15936T, with a similarity of 94.1% and 94.8%, respectively. The 16S rRNA gene sequence similarity between the two strains was 96.6%. These novel strains were found to represent new taxa of the Marinilabiliaceae family, and we propose the names Plebeiobacterium marinum gen. nov., sp. nov. and Plebeiobacterium sediminum sp. nov. with type strains D04T (MCCC 1H00493T = KCTC 92026T) and AATT (MCCC 1H00485T = KCTC 92028T), respectively. In this study, nitrogen fixation genes were predicted for 53 strains from the whole order Marinilabiliales and it was found that nitrogen fixation gene clusters were present in 26 strains. These gene clusters were found in every family in the order, highlighting that the presence of nitrogen-fixing gene clusters in the order is common. Nitrogen-fixing bacteria in sediments play an important role in various biogeochemical cycles. Thus, understanding the oceanic nitrogen cycle can provide insights into the energy flow of marine systems.